Validity of Discovery Learning-Based E-module with Video Demonstration on Reaction Rate Material for High School Student - Purti Permatasari; Hardeli Hardeli; Bundani Sakinah Alora; Sri Mulyani (Jurnal Penelitian Pendidikan IPA, 2022)
This research aims to determine the validity of the discovery learning-based E-module with a video demonstration on reaction rate material for high school students. The type of research carried out is development research with the Plomp development model. This research involved three chemistry lecturers of the Faculty of Mathematics and Natural Sciences of Universitas Negeri Padang and two high school chemistry teachers. The advice of expert reviews and students was used as the basis for module evaluation by researchers using a validity questionnaire—the Aiken's V formula processed module validity tests from chemistry lecturers and chemistry teachers. According to the findings, the developed e-module has an Aiken V value of 0.88 and is classified as valid